NAVIGATING THE INTERPLAY OF TERMINOLOGY, LANGUAGE, AND KNOWLEDGE (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This scientific article explores the intricate relationship between terminology, science, and language. It delves into the ways in which terminology shapes our understanding of the world, both scientifically and linguistically. Through an in-depth analysis of relevant literature, this article examines the impact of precise terminology on scientific communication and knowledge dissemination. Furthermore, it investigates how language, as a vehicle for expressing scientific concepts, influences the development of terminologies. The article also discusses the challenges and nuances associated with terminology in interdisciplinary fields. By highlighting these aspects, this study contributes to a comprehensive understanding of the role of terminology in shaping our scientific and linguistic worldview.